Does venue quality drive loyalty through satisfaction? Evidence from Indonesian concert attendees in Indonesia and Singapore - Fetty Nurmala Rossi; Yustisia Pasfatima Mbulu; Azra Mashita; Intan Nur Syafiqah; Fajar Anugrah Subhi (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2026)
The growth of the event industry in Southeast Asia has heightened the importance of venue quality in delivering a successful event experience. The quality of the venue plays a significant role in shaping visitor satisfaction and loyalty, especially at large-scale international concerts. This study aims to compare the effect of venue quality on visitor loyalty mediated by satisfaction at Coldplay concerts held at Gelora Bung Karno and National Stadium Singapore. Dimensions of venue quality include interaction, environment, and value. This study employs a quantitative approach based on Structural Equating Modelling (SEM) with SmartPLS 3.2.9. The study population consisted of 230 Indonesian visitors who attended Coldplay concert at both venues, with 115 respondents from each venue selected through purposive sampling. The findings indicate that the quality of interactions between staff and visitors, as well as the venue environment, including facilities and atmosphere, are key determinants of visitor satisfaction and loyalty. Meanwhile, value does not affect satisfaction at the National Stadium Singapore. This study contributes to the event management literature by providing comparative insights into venue quality in large-scale international concerts.